Penerapan Terapi Relaksasi Benson terhadap Perubahan Tekanan Darah pada Pasien Hemodialisa di Rumah Sakit Palembang - Rizki Berliana; Aniska Indah Fari; Sanny Frisca (Lembaga Pengembangan Kinerja Dosen, 2025)
Chronic kidney disease (CKD) that is left untreated can lead to serious complications, one of which is hypertension in hemodialysis patients. Intradialytic hypertension can impair quality of life and increase mortality risk. Benson relaxation therapy, which combines breathing techniques with the repetition of positive words, has the potential to lower blood pressure. The purpose of this research is to measured blood pressure during and subsequent to Benson relaxation therapy in hemodialysis patients. This quantitative research employed a pre-experimental methodological approach with a case study approach. The subjects consisted of 3 respondents selected from a population of 24 hemodialysis patients at a hospital. Blood pressure data were collected using a digital sphygmomanometer and analyzed descriptively. After three sessions of Benson relaxation therapy lasting approximately 10 minutes each, systolic blood pressure decreased with the maximum reduction of 18 mmHg and the lowest reduction of 2 mmHg, while diastolic blood pressure decreased with the maximum reduction of 20 mmHg and the lowest reduction of 1 mmHg. Benson relaxation therapy can reduce blood pressure in patients undergoing hemodialysis. Benson relaxation therapy may be considered as a non-pharmacological intervention to help lower blood pressure in hemodialysis patients. After three sessions of Benson relaxation therapy lasting approximately 10 minutes each, systolic blood pressure decreased with the maximum reduction of 18 mmHg and the lowest reduction of 2 mmHg, while diastolic blood pressure decreased with the maximum reduction of 20 mmHg and the lowest reduction of 1 mmHg. These results indicate that Benson relaxation therapy can significantly reduce blood pressure in hemodialysis patients. The therapy’s effectiveness in reducing blood pressure may be attributed to the deep breathing exercises and the relaxation response it induces, which helps to reduce the overall stress on the cardiovascular system.